2022
DOI: 10.1186/s12885-022-10396-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, severity, and factors associated with clinically significant drug-drug interactions among patients with cancer attending Mbarara Regional Referral Hospital Cancer Unit, Uganda

Abstract: Background Cancer is a major public health problem with pharmacotherapy being the cornerstone of its management. Cancer patients receive multiple drugs concurrently risking Drug-Drug Interactions (DDIs). DDIs, though avoidable, can significantly contribute to morbidity, mortality, and increased healthcare costs in this population of patients. Currently, there is no published study from Uganda on clinically significant DDIs (cs-DDIs) among cancer patients. This study identifies frequency, severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
2
0
1
Order By: Relevance
“…This finding agrees with studies conducted in Brazil,60 Pakistan,25 48 the USA,40 India28 and Taiwan 17. This might be due to cancer-related illnesses and treatment side effects, such as pain and adverse drug reactions, which demand pharmacological intervention and expose individuals to polypharmacy, a known risk factor of DDIs 61. This guides the development of preventive interventions for medication discrepancy, such as the inclusion of clinical pharmacists in the healthcare management team at the cancer unit, who can minimise DDIs by performing medication reconciliation 62.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding agrees with studies conducted in Brazil,60 Pakistan,25 48 the USA,40 India28 and Taiwan 17. This might be due to cancer-related illnesses and treatment side effects, such as pain and adverse drug reactions, which demand pharmacological intervention and expose individuals to polypharmacy, a known risk factor of DDIs 61. This guides the development of preventive interventions for medication discrepancy, such as the inclusion of clinical pharmacists in the healthcare management team at the cancer unit, who can minimise DDIs by performing medication reconciliation 62.…”
Section: Discussionsupporting
confidence: 90%
“… 17 This might be due to cancer-related illnesses and treatment side effects, such as pain and adverse drug reactions, which demand pharmacological intervention and expose individuals to polypharmacy, a known risk factor of DDIs. 61 This guides the development of preventive interventions for medication discrepancy, such as the inclusion of clinical pharmacists in the healthcare management team at the cancer unit, who can minimise DDIs by performing medication reconciliation. 62 In addition, because polypharmacy is common among patients with cancer, screening of prescribed drugs is necessary for prompt prediction, avoidance or reduction of any undesirable negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted by Lubinga and Uwiduhaye in 2011, 23% of in-patient prescriptions in Mbarara Regional Referral Hospital had potential DDIs [ 7 ]. A recent cross-sectional study conducted in the oncology unit of the same hospital revealed a 60.3% prevalence of clinically significant DDIs among chemotherapy patients, majority of whom (79.9%) were outpatients [ 14 ]. To the best of our knowledge, there is no country wide study that explored the prevalence of potential DDIs in Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…Farklı ülkelerdeki hematoloji kliniğinde yürütülen çalışmalarda, potansiyel ilaç etkileşimlerinin oranının %40-78 arasında olduğu belirtilmektedir [1,[9][10][11][12]. Hematoloji kliniğinde ayakta tedavi alan hastaların tedavisinde kullanılan ve ilaç etkileşimine sık karşılaşılan ilaçlar arasında, flukonazol, sülfametoksazol-trimetoprim, doksorubisin, siklofosfamid ve metotreksat yer almaktadır [1,12,13]. Kemik iliği transplantasyonu sürecinde tedavide sıklıkla kullanılan busulfan, siklofosfamid, etoposit gibi birçok etken madde CYP450 izoenzimleriyle metabolize ve eliminize edilmektedir.…”
Section: Introductionunclassified